2007
DOI: 10.1152/ajpcell.00224.2007
|View full text |Cite
|
Sign up to set email alerts
|

Role of DDAH-1 in lipid peroxidation product-mediated inhibition of endothelial NO generation

Abstract: Altered nitric oxide (NO) biosynthesis is thought to play a role in the initiation and progression of atherosclerosis and may contribute to increased risk seen in other cardiovascular diseases. It is hypothesized that altered NO bioavailability may result from an increase in endogenous NO synthase (NOS) inhibitors, asymmetric dimethly araginine (ADMA), and N(G)-monomethyl arginine, which are normally metabolized by dimethyarginine dimethylamine hydrolase (DDAH). Lipid hydroperoxides and their degradation produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 46 publications
0
35
1
1
Order By: Relevance
“…Currently, no evidence indicates that hyperglycemia or oxidative stress regulates PRMT activity. However, studies in vitro demonstrate that incubation of endothelial cells with glucose or end products of lipid peroxidation increases ADMA by suppressing its DDAH-dependent degradation [39,40]. In contrast, our work indicates that postprandial concentrations of ADMA are unaffected following glucose ingestion.…”
Section: Discussioncontrasting
confidence: 53%
“…Currently, no evidence indicates that hyperglycemia or oxidative stress regulates PRMT activity. However, studies in vitro demonstrate that incubation of endothelial cells with glucose or end products of lipid peroxidation increases ADMA by suppressing its DDAH-dependent degradation [39,40]. In contrast, our work indicates that postprandial concentrations of ADMA are unaffected following glucose ingestion.…”
Section: Discussioncontrasting
confidence: 53%
“…Recently, several groups have demonstrated that modulating DDAH activity can have a profound effect on endothelial NO production (8, 9, 11, 20, 21, 23-25, 34, 35). In this regard, our group and others have shown that overexpression of DDAH-1 results in increased NO production (9,36). Furthermore, oxidized low density lipoprotein and tumor necrosis factor ␣ have been shown to decrease DDAH activity, leading to decreased endothelial NO production (37).…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, oxidized low density lipoprotein and tumor necrosis factor ␣ have been shown to decrease DDAH activity, leading to decreased endothelial NO production (37). It has also been demonstrated that 4-hyrdoxynonenal, the highly reactive oxidant product of lipid peroxidation, inhibits DDAH activity and leads to impaired NO generation through the formation of Michael addition products in the catalytic triad of DDAH (36). Thus, evidence suggests that DDAH-1 activity is under redox control, and loss of enzyme function impairs endothelial NO generation.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress impairs effective NO activity in several ways: oxidizing tetrahydrobiopterin; inhibiting dimethylarginine dimethylaminohydrolase (DDAH), and thereby boosting intracellular levels of the eNOS inhibitor/uncoupler asymmetric dimethylarginine (ADMA) [115,116,117,118,119]; and direct quenching of NO by superoxide, leading to production of the potent oxidant peroxynitrite. Peroxynitrite is a mediator of the oxidation of tetrahydrobiopterin; and it can also inhibit a key target of NO bioactivity, soluble guanylate cyclase (sGC), by oxidizing the ferrous iron in its attached heme group [120,121,122,123].…”
Section: High-dose Folate Combats Enos Uncouplingmentioning
confidence: 99%